2022
DOI: 10.37193/cmi.2022.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Some inequalities on the Mostar index

Abstract: "Topological indices are the numerical descriptors of a molecular structure obtained via molecular graph G. They are used to predict physicochemical and bioactive properties of the molecules and molecular compounds. In this paper, the Mostar index is studied. It is presented the relationships between the Mostar index and other topological indices. Inequalities about some parameters and also Nordhaus-Gaddum-type results for the Mostar index are also presented."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…In recent years, these indices have gained significant attention due to their potential applications in drug discovery, material science, and network analysis. Havare 8 , 25 studied the Mostar index of bridge graphs and showed its relevance in modeling the electronic properties of nanotubes. Similarly, the study by Kier and Hall demonstrated the usefulness of the Zagreb and Forgotten indices in predicting the toxicity and bioactivity of chemical compounds.…”
Section: Motivationmentioning
confidence: 99%
“…In recent years, these indices have gained significant attention due to their potential applications in drug discovery, material science, and network analysis. Havare 8 , 25 studied the Mostar index of bridge graphs and showed its relevance in modeling the electronic properties of nanotubes. Similarly, the study by Kier and Hall demonstrated the usefulness of the Zagreb and Forgotten indices in predicting the toxicity and bioactivity of chemical compounds.…”
Section: Motivationmentioning
confidence: 99%